2019
DOI: 10.3390/su11030827
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Emotional Intelligence Test (MEIT): An Ability Test to Assess Emotional Intelligence at Work

Abstract: The present study analyzes the Mobile Emotional Intelligence Test (MEIT), a new ability-test to assess emotional intelligence (EI) in a digital way. Taking into account the importance of emotional competencies in the study of employees’ wellbeing and performance, the instrument tested is based on the most supported ability model (Four-branch Mayer and Salovey Model), and it evaluates emotional capacity through nine different emotional tasks. A total of 1549 participants (841 women and 708 men) with an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…Previous research has confirmed that self-reported and EI ability tests may differ in their predictive validity with respect to work outcomes (Miao et al, 2017). Future studies should therefore combine selfreporting measures with EI performance tests (Mayer et al, 2016), or even consider new proposals adapted to the organizational context, such as the Mobile Emotional Intelligence Test (Sanchez-Gomez & Breso, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has confirmed that self-reported and EI ability tests may differ in their predictive validity with respect to work outcomes (Miao et al, 2017). Future studies should therefore combine selfreporting measures with EI performance tests (Mayer et al, 2016), or even consider new proposals adapted to the organizational context, such as the Mobile Emotional Intelligence Test (Sanchez-Gomez & Breso, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in line with prior research examining predictive and incremental validity [ 63 ], an ability EI test such as MSCEIT [ 64 ] or MEIT [ 16 ] should be used. Yet, WLEIS is still one of the most used instruments to measure EI [ 65 ], and it has been designed specifically to assess the branches proposed by Mayer and Salovey’s model [ 16 ]. Furthermore, self-report questionnaires have some advantages, for instance, they can be administered and completed in less time [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is recommended to use both self-reports and performance tests to measure EI [12]. Therefore, in line with prior research examining predictive and incremental validity [63], an ability EI test such as MSCEIT [64] or MEIT [16] should be used. Yet, WLEIS is still one of the most used instruments to measure EI [65], and it has been designed specifically to assess the branches proposed by Mayer and Salovey's model [16].…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Labor Office (ILO) has recommended that factors such as fear of job loss, pay cuts, layoffs and reduced benefits shall be properly assessed [ 20 ]. Despite these recommendations, the assessment of economic-related factors in the workplace lacks reliable methods and has often been performed by outdated tools [ 21 ]. In this regard, Giorgi and colleagues [ 22 ] proposed an innovative tool aimed at measuring fear of economic crisis defined as “the individual’s perception of the crisis’ potential negative effect on his or her job, as well as on his or her organization” (p. 139).…”
Section: Introductionmentioning
confidence: 99%